2018
DOI: 10.1002/elps.201700457
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous identification of the anaphylactoid components from traditional Chinese medicine injections using rat basophilic leukemia 2H3 and laboratory of allergic disease 2 dual‐mixed/cell membrane chromatography model

Abstract: Traditional Chinese medicine (TCM) has been used for prevention and treatment of various diseases for many decades. TCM injection is a new dosage form, with incidence of anaphylactoid reactions increasing every year. In this study, the rat basophilic leukemia 2H3 (RBL-2H3) and laboratory of allergic disease 2 (LAD2) dual-mixed/CMC was established and was coupled with an HPLC-ESI-IT-TOF-MS system to identify the potential allergenic components in Haqing injection. Cinobufagin, piperine, osthole, praeruptorin A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…It also suppresses MRGPRX2 expression on the plasma membrane, and thus, MRGPRX2 is inhibited through a complex mechanism [ 153 ]. In addition, Osthole has also been reported to bind to IgE receptors, which may indicate an anti-inflammatory effect of dual action on MCs [ 154 ]. In addition, dexamethasone, a well-known anti-inflammatory drug, inhibits MC activation through downregulating Gαi and MRGPRX2 downstream signals induced by basic secretagogues [ 155 ].…”
Section: Mrgprx2 Inhibitorsmentioning
confidence: 99%
“…It also suppresses MRGPRX2 expression on the plasma membrane, and thus, MRGPRX2 is inhibited through a complex mechanism [ 153 ]. In addition, Osthole has also been reported to bind to IgE receptors, which may indicate an anti-inflammatory effect of dual action on MCs [ 154 ]. In addition, dexamethasone, a well-known anti-inflammatory drug, inhibits MC activation through downregulating Gαi and MRGPRX2 downstream signals induced by basic secretagogues [ 155 ].…”
Section: Mrgprx2 Inhibitorsmentioning
confidence: 99%
“…Exogenous ligands of MRGPRX2 include the cationic polymer compound 48/80 (C48/80), which is commonly used in receptor functional assays, and a variety of drugs approved by the Food and Drug Administration (FDA), such as fluoroquinolones (e.g., ciprofloxacin), neuromuscular blocking agents (e.g., rocuronium, atracurium), opioids (e.g., morphine), and many others [ 4 , 9 , 28 ]. MRGPRX2 can also be activated or inhibited by other exogenous agents, such as bacterial quorum sensing proteins, insect venoms [ 3 , 29 , 30 ], or many different plant xenobiotics ( Figure 1 ) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]; representatives of which are described in the following part of this review.…”
Section: Pathophysiological Basismentioning
confidence: 99%
“…Praeruptorins have many beneficial physiological effects in the treatment of upper respiratory tract infections, cardiovascular, immune, and nervous system diseases [ 106 ]. One of these biological compounds is praeruptorin A, which exhibits several bioactive properties ( Table 1 ) and has been studied in the context of MC activation via MRGPRX2 [ 38 ]. A competitive binding assay showed that this compound competes with ciprofloxacin for binding to MRGPRX2, suggesting that it may interact directly with the receptor [ 38 ].…”
Section: Traditional Chinese Medicines and Plant-derived Compoundsmentioning
confidence: 99%
“…Using multiple CMs to prepare a CM chromatographic column can reduce the aforementioned disadvantage. According to this view, Han et al proposed the double mixture/CMC model for the first time (Han et al, 2018). The rat basophilic leukemia 2H3 (RBL‐2H3) and laboratory of allergic disease 2 (LAD2) dual‐mixed/CMC was created in their investigation, and it was connected with an HPLC‐ESI‐IT‐TOF‐MS system to detect probable allergenic components in Haqing injection, and cinobufagin, piperine, osthole, praeruptorin A, and schizandrin A were screened out.…”
Section: Applications Of Immobilized Biomembrane Materialsmentioning
confidence: 99%